Conceptions et enjeux de changement: la complexité occultée - Michaud, Clemence; Chabot, Jean-Charles (Canadian Journal of Higher Education, 2005)
Current research articles often present the concept of change as if it were a stable constant incurring the effects of instability. This present article, borrowing the concepts of knowledge-power and of discourse from Foucault, sees this discourse as only one discourse among many. Inspired by a variety of theories of education, we propose six approaches to change (adaptive, organismic, transpersonal, transformative, societal, and interactional). Each of these approaches is discussed in terms of the intentions, objectives, and indicators of change they privilege. Viewing the issues surrounding change from the perspective of the interaction of a variety of approaches could constitute a workable strategy for the introduction of reforms and for the designing of training programs.